Hasan Al-Banna's Thought Contribution to the Concept of Islamic Education - Putri, Yulita; Nurhuda, Abid (International Journal of Contemporary Studies in Education, 2023)
Education will always proceed in human civilization because it really functions for the welfare of their lives. Westerners are no exception, who are also increasingly showing their existence as centers of civilization, so that Islamic thinkers emerged, one of whom is Hasan Albanna. And the purpose of this study is to describe the contribution of Hasan Al-Banna's thought to the concept of Islamic education. The method used is descriptive qualitative with a literature study approach. The results of the study show that the contribution of Hasan Al-Banna's thoughts to the concept of Islamic education includes the basis of education consisting of the Qur'an, Assunnah and Amaliyah Friends. Then educational goals consist of permanent and contextual goals. Then educational material must be balanced between the world and the hereafter so that various aspects are needed, starting from aqidah to social. Then the educational method which consists of exemplary, punishment, story, habituation and experience. And finally, there is an evaluation of education with a muhasabah model so that the value of honesty arises in oneself.